PENGARUH KETELADANAN ORANG TUA DAN GURU TERHADAP AKHLAK SISWA DI SEKOLAH MENENGAH ATAS (SMA) NEGERI 6 BENGKULU SELATAN - Wiwi Okta Lestari (UIN Fatmawati Sukarno Bengkulu, 2020)
Abstract: This study aimed to determine the effect of exemplary morals of parents of students, to know exemplary morals of teachers to students and to identify exemplary parents and teachers against the morals of students at SMAN 6 South Bengkulu. This research method is quantitative method by using a simple correlation and regression. The study population was student/student class X SMA 6 South Bengkulu, amounting to 238 people, while a sample in this study was 25% of the population of 60 people. The results of the study that the influence of exemplary parents and teachers to the character class X State Senior High School 6 South Bengkulu 2016, can be summarized as follows: First, there is a very significant influence among the exemplary morals of parents of students. From the calculation of the correlation between X1 to Y at 0.581 and regression equation Y = 26.619 + 0.581. Second, there is significant influence between the exemplary morals of teachers to students. From the calculation of the correlation between X2 on Y at 0.033 and regression equation Y = 8.258 + 0.033. Third, there is a very significant influence among exemplary parents and teachers jointly or individually against the morals of students. From the results of the correlation calculation by using multiple regression analysis obtained correlation R anatara price X1 and X2 together to Y at 0.583 and regression equation Y = 14.684 + 0.587 + 0.045.